Identifikasi Penjalaran Gelombang Panjang Samudera Hindia Ke Selat Lombok Berdasarkan Komponen Harmonik Arus - Yogo Pratomo; Widodo Setiyo Pranowo; Hendrawan Setiadi (Journal Omni-Akuatika, 2016)
The Lombok Strait is one area passing by seawater mass from Pacific Ocean to Indian Ocean, well known as Indonesia Through Flow (ARLINDO). It was profen by the existane of long periode harmonic current component affected by the sun (SA, SSA ) , and an influence by moon (MSF). The harmonic current speed has an average of 0.370668 m/s in the depths of 100 meters during January 9, 2004 until 14 June 2005 (1.5 years). Time series data ocean current of INSTANT project (2004-2005) is used in this research, analized by using toolbox module of t-tide 1.3 beta. The current rose at 350 meters deep and 450 meters deep shous pattern of the a unique ocean current, which mastly toward to north and northeast (55 %) with velocity at 0.2-1.0 m/s. The current is coming from Indian Ocean which proven by the existence of components like M4, MS4, MSF, O1. There is also ocean current toward to south and southwest as (45 %) with speed of 0.11-0.9 m/s. Thie ocean current which coming from Indian Ocean is indication of propagation of long wave penetration to Lombok Strait. During its propagation passing the sill, the wave become an internal wave in Lombok Strait.Keywords: internal wave, indian ocean, lombok strait, harmonic currents component, INSTANT 2004-2005